Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I try to use the method of differentiation under integral sign for the first one And integrate it back, but I failed to find the constant $c$ .... Anyone hav other method? $$\begin{align} & \int_{0}^{\frac{\pi }{2}}{{{x}^{2}}{{\ln }^{2}}\left( 2\cos x \right)\text{d}x} \\ & \int_{0}^{\frac{\pi }{3}}{x{{\ln }^{2}}\left( 2\sin \frac{x}{2} \right)}\text{d}x \\ \end{align}$$

share|improve this question
1  
Do you have any reason to think these have closed-form expressions? –  Robert Israel Jan 29 '13 at 8:07
    
@RobertIsrael I think these are likely to hav one –  Ryan Jan 30 '13 at 2:20
1  
Do you have any reason for that thought? –  Robert Israel Jan 30 '13 at 7:05
add comment

2 Answers 2

up vote 3 down vote accepted

From \begin{equation} \int_{0}^{\frac{\pi }{2}}\left( 2\cos \theta \right) ^{x}\cos y\theta d\theta =\frac{\pi }{2}F(1+\frac{x+y}{2},1+\frac{x-y}{2}), \tag*{(1)} \end{equation} where $F(x,y)=\frac{\Gamma (x+y-1)}{\Gamma (x)\Gamma (y)},$ we can get that \begin{equation} \begin{array}{c} \int_{0}^{\frac{\pi }{2}}\theta ^{q}\left( 2\cos \theta \right) ^{x}\cos \frac{2y\theta +q\pi }{2}\ln ^{p}\left( 2\cos \theta \right) d\theta \\ =\frac{\pi }{2^{p+q+1}}\sum\limits_{k=0}^{q}(-1)^{q-k}C_{q}^{k}\sum \limits_{j=0}^{p}C_{p}^{j}F_{k+j,q+p-k-j}(1+\frac{x+y}{2},1+\frac{x-y}{2}) \end{array} \tag*{(2)} \end{equation} In (2) let $x,y=0,q$ replaced by $2q$ we have \begin{equation} \int_{0}^{\frac{\pi }{2}}\theta ^{2q}\ln ^{p}\left( 2\cos \theta \right) d\theta =\frac{\pi }{2^{p+q+1}}\sum\limits_{k=0}^{2q}(-1)^{q-k}C_{2q}^{k} \sum\limits_{j=0}^{p}C_{p}^{j}F_{k+j,2q+p-k-j}(1,1) \tag*{(3)} \end{equation} For $F_{p,qj}(1,1)$ there is the following recurrence relations \begin{equation} F_{p,q}(1,1)=p!(q-1)!\sum\limits_{k=0}^{p-1}\sum \limits_{j=0}^{q-1}C_{p+q-1-k-j}^{p-k}\frac{(-1)^{p+q-k-j}\zeta (p+q-k-j) }{k!j!}F_{k,j}(1,1). \tag*{(4)} \end{equation} By (4) we can get that \begin{equation} \begin{array}{c} F_{0,0}(1,1)=1,F_{0,i}(1,1)=0,i=1,2,3,4,F_{1,1}(1,1)=\frac{\pi ^{2}}{6}, \\ F_{1,2}(1,1)=-2\zeta (3),F_{1,3}(1,1)=\frac{\pi ^{4}}{15},F_{1,4}(1,1)=-24 \zeta (5), \\ F_{2,2}(1,1)=\frac{\pi ^{4}}{90},F_{2,3}(1,1)=-2\pi ^{2}\zeta (3)-24\zeta (5), \\ F_{2,4}(1,1)=\frac{68\pi ^{6}}{315}+24\zeta ^{2}(3),F_{3,3}(1,1)=\frac{ 107\pi ^{6}}{420}+36\zeta ^{2}(3), \\ F_{3,4}(1,1)=-6\pi ^{4}\zeta (3)-48\pi ^{2}\zeta (5)-720\zeta (7), \\ F_{4,4}(1,1)=\frac{3701\pi ^{8}}{3150}+96\pi ^{2}\zeta ^{2}(3)-2304\zeta (3)\zeta (5), \end{array} \tag*{(5)} \end{equation} By (3) and (5) we have \begin{equation} \int_{0}^{\frac{\pi }{2}}\theta ^{2}\ln ^{2}\left( 2\cos \theta \right) d\theta =\frac{11\pi ^{5}}{1440} \tag*{(6)} \end{equation}

share|improve this answer
add comment

A related problem. One can manage to get the following closed form solution for the second integral,

$$\int_{0}^{\frac{\pi }{3}}{x{{\ln }^{2}}\left( 2\sin \frac{x}{2} \right)}\text{d}x = \frac{1}{4}\,{_5F_4\left(1,1,1,1,1;\,\frac{3}{2},2,2,2;\,\frac{1}{4}\right)}\sim 0.2555485412 $$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.